ChemInform Abstract: Transport Properties of the SnBi2Te4—PbBi2Te4 Solid Solution. Issue 14 (April 2015) - Pan, Lin; Li, Jing; Berardan, David; Dragoe, Nita
Abstract: The Sn1‐x Pbx Bi2 Te4 solid solution is characterized by XRD, Hall, Seebeck coefficient, electrical resistivity, thermal conductivity, and specific heat measurements.